Solving the systemic problems of the enterprises of the chemical complex by using integrated management systems - S. A. Panova; R. Yu. Tarasenko (Тонкие химические технологии)
The absence of integrated decision making systems on the enterprises of the chemical complex creates significant obstacles in the development of the industry sector. The development of integrated decision making systems will significantly enhance the pace of modernization and control of the processes in enterprises and will create additional competitive advantages for the complex as a whole.